Moringa Oleifera Ameliorates The Expression Of Collagen-1 In Tibia Bone Of Fluoride-Intoxicated Rats (Applied Biological Research, 2015)
The present study was aimed to assess the protective effect of Moringa  oleifera fruits extract against sodium fluoride induced down-regulation of  collagen-1 gene in tibia bone of rats. Twenty four albino rats were  randomly assigned to four groups. The 1st group served as control and  received only tap water. The 2nd group received sodium fluoride (200 ppm)  through drinking water. The 3rd group received extract of M. oleifera alone  and 4th group received M. oleifera extract alongwith fluorinated drinking  water, daily by gavage for 8 weeks. Significant decrease in the expression  of collagen-1 gene in tibia bone was noted in fluoride treated rats.  of M. oleifera fruits extract during exposure to fluoride  up-regulated the expression of collagen-1 gene in tibia bone as compared to  untreated fluoride exposed rats. It is concluded that daily oral  administration of M. oleifera fruit extract has positive influence on the  expression of collagen-1 gene in bones of fluoride intoxicated rats.
Keywords: Collagen-1; gene expression; fluoride; Moringa oleifera; rats